2018
DOI: 10.14569/ijacsa.2018.090503
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic-Controlled 6-DOF Robotic Arm Color-based Sorter with Machine Vision Feedback

Abstract: A demonstration of the application of fuzzy logicbased joint controller (FLJC) to a 6-DOF robotic arm as a colorbased sorter system is presented in this study. The robotic arm with FLJC is integrated with a machine vision system that can discriminate different colors. Additionally, the machine vision system composed of Kinect camera and computer were used to extract the coordinates of the gripper and the objects within the image of the workspace. A graphical user interface with an underlying sorting algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In his article, Jia does not explain the inverse kinematics mechanism used, but rather focuses on detection systems and electronic hardware. Abad [17] proposed a Fuzzy Logic Based Joint (FLJC) control system on a 6-DOF manipulator for color-based sorting applications with one camera. The main difficulty of FJLC is determining the membership function for each state and the optimal fuzzy rules for each angle of the manipulator.…”
Section: Imentioning
confidence: 99%
See 1 more Smart Citation
“…In his article, Jia does not explain the inverse kinematics mechanism used, but rather focuses on detection systems and electronic hardware. Abad [17] proposed a Fuzzy Logic Based Joint (FLJC) control system on a 6-DOF manipulator for color-based sorting applications with one camera. The main difficulty of FJLC is determining the membership function for each state and the optimal fuzzy rules for each angle of the manipulator.…”
Section: Imentioning
confidence: 99%
“…∆ can be assumed as linear velocity EE linear and ∆ assumed as angular velocity. The linear velocity of EE is controlled with a proportional derivative (PD) control with ( 15)- (17).…”
Section: Mechanical Design and Framework Systemmentioning
confidence: 99%
“…In closed-loop dominion systems, the classical controller has been replaced by the FLC. This quantity that the IF-THEN rules and fuzzy membership functions replace the mathematical rule to experiment the system [2]. For the fuzzy logic mechanism, the signal variables are error (e) and derivative of error (de/dt), and the output Sus_def (suspension deflection) (u).…”
Section: Fuzzy Controller Designmentioning
confidence: 99%
“…Liu proposed that robots equipped with machine vision-based manipulators could efficiently perform tasks such as logistics courier sorting and fruit picking in orchards [4]. Abad et al found through field experiments that machine vision was able to achieve at least 95% accuracy in color discrimination of stacked colored objects [5]. Nair et al found that the application of machine vision for image analysis helped in classifying flood zones and had an accuracy of 83.1% [6].…”
Section: Introductionmentioning
confidence: 99%